A framework to characterize young school children's individual mathematical creativity—an integrative review. Issue 1 (March 2023) - Bruhn, Svenja; Lüken, Miriam M.
Both educational policies and current mathematics education research highlight that all students should be given the opportunity to be creative in mathematics class. However, if creativity is of such significance to mathematics learning, how can we describe the mathematical creativity of school children? Conducting an integrative literature review, this article aims to answer this question by synthesizing conceptual aspects and research results on the mathematical creativity of young school children working on mathematical open tasks. Here, concepts of creativity in mathematics education based on a divergent production approach are emphasized in detail. This leads to the introduction of the term "individual mathematical creativity" and to the suggestion of a framework to qualitatively characterize the individual mathematical creativity of school children working on open tasks. Its relevance and application as a scientific and/or educational tool to analyze and foster the creativity of students are explained exemplarily using the creative task processing of the 6-year-old student Jessica.